The interaction between a keystone plant species and its dominant epiphyte on Marion Island : climate change implications - Buwa, Ziphokazi Siyasanga (Stellenbosch : Stellenbosch University, 2007)
Thesis (MSc)--University of Stellenbosch, 2007. ENGLISH ABSTRACT: Climate has shown some remarkable changes over the past century, especially at the polar and sub-polar regions. Southern Ocean Islands provide good models for studies related to climate change effects, since effects may be evident in the short term and may also be clearer. Marion Island is an example of such a system with a harsh abiotic environment, and low species richness often vulnerable to change. Climate change is predicted, and also reported, to have biological consequences on plant communities, affecting the phenology, morphology, and the interaction between individuals and species. This study examines the association between the keystone plant species, Azorella selago Hook. (Apiaceace), and its dominant epiphyte Agrostis magellanica Lam. (Poaceae). Two complimentary approaches were used, one observational and the other experimental. The main objective for the observational study was to quantify bioticallyrelevant microclimate temperature, as well as the morphology, epiphyte load and phenology of A. selago at three different altitude sites on Marion Island. This provided information on baseline variation for understanding specific variability in plant response to the experimental part of this study, against which future patterns arising from biological monitoring can be compared. Studying plants at different altitudes provides a possible analogue for temperature-related climate change consequences for the ecology of A. selago, and its interaction with A. magellanica. The microclimate temperature associated with A. selago differed between the three sites examined. This difference was related to local topographic conditions and altitude differences. Cushion size differed distinctively between the three altitude sites, with this difference related to environmental heterogeneity such as differences in age and substrate structure. Azorella selago annual growth rate was estimated through stem length and the number of leaves on both exposed and ...